FACTORS INFLUENCING WEST KALIMANTAN PROVINCE STUDENTS CONTINUE STUDYING ACCOUNTING - Wijaya, Vallery Revica; Lukman, Hendro (Graduate Program of Universitas Tarumanagara, 2024)
This study aims to determine and analyze the effect of career, income and prestige motivation on students' interest in continuing their studies in accounting. The population is students in West Kalimantan province and the sample was 115 students in the cities of Pontianak and Singkawang. The sampling technique uses nonprobability sampling with primary data obtained through distributing questionnaires using the Google Form platform. The data analysis methods used are path coefficient, coefficient of determination (R2), and multiple linear regression analysis using the SmartPLS (Partial Least Square) application version 4. The results of the research show that career, income and prestige motivation effect students' interest in continuing their studies in accounting.